Tanggung Jawab Notaris yang Memalsukan Akta Perjanjian Pengikatan Jual Beli dan Kuasa Menjual (Studi Atas Putusan Pengadilan Negeri Denpasar Nomor 89/Pid.B/2020/PN.Dps) - Putri Ayu Salamah S. (Officium Notarium, 2021)
This research examines the responsibility of a Notary who falsifies the Deed of Sale and Purchase Agreement and Authorization to Sell by conducting a study on the Denpasar District Court Decision Number 89/Pid.B/2020/PN.Dps. The problems formulated in this research are first, how is the responsibility of the Notary who falsifies the Sale and Purchase Binding Agreement and Sales Authorization Deed and second, how is the implementation of the responsibility to the Notary who falsifies the Sale and Purchase Binding Agreement and Selling Authorization Deed. This is a normative legal research with a statutory approach and analyzed using qualitative analysis methods. The results of this study conclude that first, responsibility of the Notary who falsifies the Deed of Binding Sale and Purchase Agreement and the Power to Sell is to provide sanctions, both administrative sanctions for violating several provisions in the Notary Position Act, civil sanctions due to the falsification of the deed has been cause harm to the owner of the original Certificate of Ownership, and criminal sanctions because the actions of the Notary have fulfilled the elements of a criminal act as regulated in Article 264 paragraph (1) Letter a of the Criminal Code jo. Article 88 of the Criminal Code. Second, the implementation of these responsibilities is not fully in accordance with what is regulated in the law. If it is based on the provisions of Article 13 of the Law on Notary Positions and Permenkumham Number 16 of 2016 concerning Procedures for Imposing Administrative Sanctions Against Notaries, the sanction given to notaries is dishonorable dismissal which causes the notary to have to submit the protocol and can no longer accept work in whatever form, but in reality the notary is still practicing in his position as a notary which can be concluded that the administrative sanctions given to the notary are not dishonorable dismissal. While the civil and criminal sanctions given are in accordance with what is regulated in the law, namely by giving a prison sentence of 2 months to a Notary.Key Word: Notary Responsibility, Deed Forgery, Authentic Deed, Application AbstrakTesis ini meneliti tentang tanggung jawab Notaris yang memalsukan Akta Perjanjian Pengikatan Jual Beli dan Kuasa Menjual dengan melakukan studi atas Putusan Pengadilan Negeri Denpasar Nomor 89/Pid.B/2020/PN.Dps. Masalah yang dirumuskan dalam penelitian ini, pertama, bagaimana tanggung jawab Notaris yang memalsukan Akta Perjanjian Pengikatan Jual Beli dan Kuasa Menjual dan kedua, bagaimana penerapan dari tanggung jawab kepada Notaris yang memalsukan Akta Perjanjian Pengikatan Jual Beli dan Kuasa Menjual. Jenis penelitian ini adalah penelitian hukum normatif dengan pendekatan perundang-undangan dan dianalisis dengan menggunakan metode analisa kualitatif. Hasil penelitian ini menyimpulkan, pertama tanggung jawab dari Notaris yang memalsukan Akta Perjanjian Pengikatan Jual Beli dan Kuasa Menjual ialah dengan pemberian sanksi baik itu sanksi administratif karena telah melanggar beberapa ketentuan dalam Undang-Undang Jabatan Notaris, sanksi perdata karena akibat adanya pemalsuan akta tersebut telah menimbulkan kerugian bagi pemilik dari Sertifikat Hak Milik yang asli, dan sanksi pidana karena perbuatan Notaris telah memenuhi unsur-unsur tindak pidana yang diatur dalam Pasal 264 ayat (1) Huruf a KUHP jo. Pasal 88 KUHP. Kedua, penerapan dari tanggung jawab tersebut belum sepenuhnya sesuai dengan apa yang diatur dalam undang-undang. Jika didasarkan pada ketentuan Pasal 13 Undang-Undang Jabatan Notaris dan Permenkumham Nomor 16 Tahun 2016 tentang Tata Cara Penjatuhan Sanksi Administratif Terhadap Notaris maka seharusnya sanksi yang diberikan kepada notaris adalah pemberhentian dengan tidak hormat yang menyebabkan notaris harus menyerahkan protokolnya dan tidak dapat lagi menerima pekerjaan dalam bentuk apapun namun pada kenyataannya notaris tersebut masih berpraktek dalam kedudukannya sebagai notaris yang dapat disimpulkan bahwa sanksi administratif yang diberikan kepada notaris tersebut bukanlah pemberhentian dengan tidak hormat. Sedangkan sanksi perdata maupun pidana yang diberikan telah sesuai dengan apa yang di atur di dalam undang-undang yaitu dengan diberikannya hukuman pidana penjara selama 2 bulan kepada Notaris.Kata-kata Kunci: Tanggung Jawab Notaris, Pemalsuan Akta, Akta Autentik, Penerapan